Identifying Features of Cardiac Disease Phenotypes Based on Mechanical Function in a Catecholaminergic Polymorphic Ventricular Tachycardia Model - Stempien, A.; Josvai, M.; de Lange, W. J.; Hernandez, J. J.; Notbohm, J.; Kamp, T. J.; Valdivia, H. H.; Eckhardt, L. L.; Maginot, K. R.; Ralphe, J. C.; Crone, W. C. (Frontiers in Bioengineering and Biotechnology, 2022)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is characterized by an arrhythmogenic mechanism involving disruption of calcium handling. This genetic disease can lead to sudden death in children and young adults during physical or emotional stress. Prior CPVT studies have focused on calcium handling, but mechanical functionality has rarely been investigated in vitro. In this research we combine stem cell derived cardiomyocytes from a CPVT patient (RyR2-H2464D mutation) and a healthy familial control with an engineered culture platform to evaluate mechanical function of cardiomyocytes. Substrates with Young’s modulus ranging from 10 kPa to 50 kPa were used in conjunction with microcontact printing of ECM proteins into defined patterns for subsequent attachment. Digital Image Correlation (DIC) was used to evaluate collections of contracting cells. The amplitude of contractile strain was utilized as a quantitative indicator of functionality and disease severity. We found statistically significant differences; the maximum contractile strain was found to be consistently higher in patient samples compared to control samples on all substrate stiffnesses. Additionally, the patient cell line had a statistically significantly slower intrinsic contraction rate than the control, which agrees with prior literature. Differences in mechanical strain have not been previously reported, and hypercontractility is not a known characteristic of CPVT. However, functional changes can occur as the disease progresses, thus this observation may not represent behavior observed in adolescent and adult patients. These results add to the limited studies of mechanical function of CPVT CMs reported in literature and identify functional differences that should be further explored.